PENINGKATAN DAYA SAING UMKM MEBEL DI KABUPATEN SUKOHARJO MELALUI KEGIATAN IPTEK BAGI MASYARAKAT (IbM) - Sulistyono, IF Bambang; Widiyanti, Emi; Santoso, Arief Iman (Universitas Negeri Yogyakarta, 2017)
Furniture industry sector as a sector becomes the superior for developed countries in the state foreign exchange. Furniture industry products always have a higher exchange rate and profitable and can create greater value than other sectors. Furniture industry as one of the leading industries in Indonesia faces problems such as the weak competitiveness of SMEs actors in the factors of application of standard technological procedures, the process of technological mastery and business management. This is experienced by some SMEs furniture in Sukoharjo District, among them are UMKM Berkah Jaya Furniture and Totok Furniture. The activities undertaken to improve competitiveness include: (1) increasing the mastery of production technology and finishing UMKM partner furniture through the introduction of table spinser (combination of spindle and jigsaw machine) and finishing table (turntable); (2) increasing product value of both partners through mix media product training in accordance with market trends and the ability to conduct market surveys and develop networks through exhibition participation; and (3) improving business management of both partners through business assistance activities